Does anyone know how I could get a good upper bound for the following:

$$R := \prod_{\substack{ p \; \text{prime} \\ 5 \leq p < n}}p^{\frac{n}{p-1}}$$

I'm not that skilled at asymptotic analysis and the best I have been able to come up with is $\exp\left({\frac{1.01624n^2}{4}}\right)$ since $p-1 \geq 4$ for all $p \geq 5$ and:

$$\log R = n \sum_{\substack{ p \; \text{prime} \\ 5 \leq p <n}}{\frac{1}{p-1}} \log p < \frac{n}{4} \sum_{\substack{ p \; \text{prime} \\ 5 \leq p <n}} \log p < \frac{1.01624n^2}{4}$$

since the first Chebyshev function is bounded above by $1.01624n$ (I saw this bound on Wikipedia). I know that this bound is way too large though since it does not take into account that $\lim_{p \to \infty} \frac{1}{p-1} = 0$. Does anyone have any other suggestions? Thanks for your help.


Mertens second formula states $$\sum_{p\leq x}\frac{\log\left(p\right)}{p}=\log\left(x\right)+O\left(1\right)$$ so $$\log\left(\prod_{5\leq p\leq n-1}p^{\frac{n}{p-1}}\right)=n\sum_{5\leq p\leq n-1}\frac{\log\left(p\right)}{p-1}=n\sum_{p\leq n}\frac{\log\left(p\right)}{p}+O\left(n\right)=n\log\left(n\right)+O\left(n\right)$$ hence $$\prod_{5\leq p\leq n-1}p^{\frac{n}{p-1}}=e^{n\log\left(n\right)+O\left(n\right)}.$$ Expanding a little bit, the sositution holds because$$\sum_{5\leq p\leq n-1}\frac{\log\left(p\right)}{p-1}-\sum_{p\leq n-1}\frac{\log\left(p\right)}{p}=\sum_{p\leq n-1}\frac{\log\left(p\right)}{p\left(p-1\right)}-\frac{\log\left(3\right)}{2}\leq\sum_{p\geq2}\frac{\log\left(p\right)}{p\left(p-1\right)}-\frac{\log\left(3\right)}{2}=O\left(1\right)$$ because $\sum_{p\geq2}\frac{\log\left(p\right)}{p\left(p-1\right)}$ is convergent. So$$n\sum_{5\leq p\leq n-1}\frac{\log\left(p\right)}{p-1}=n\sum_{p\leq n-1}\frac{\log\left(p\right)}{p}+O\left(n\right)=n\sum_{p\leq n}\frac{\log\left(p\right)}{p}+O\left(n\right)$$ because adding the term (it's not necessary, you can find the asymptotic with $n-1$) $\log\left(n\right)/n$ gives an error of $$n\frac{\log\left(n\right)}{n}=\log\left(n\right)=O\left(n\right).$$

  • $\begingroup$ Thank you. This is probably a stupid question, but how can you change the denominator in the summation from $p-1$ to $p$ with the addition of a constant term? Couldn't it work our to be more than a constant (especially considering the factor of $n$ outside the summation)? Thanks. $\endgroup$ – Ari Mar 5 '15 at 23:57
  • $\begingroup$ @Ari There was an error, thank you. I added more details, hope it's more clear now. $\endgroup$ – Marco Cantarini Mar 6 '15 at 8:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.